2004
DOI: 10.1091/mbc.e03-07-0530
|View full text |Cite
|
Sign up to set email alerts
|

Dinitroanilines Bind α-Tubulin to Disrupt Microtubules

Abstract: Protozoan parasites are remarkably sensitive to dinitroanilines such as oryzalin, which disrupt plant but not animal microtubules. To explore the basis of dinitroaniline action, we isolated 49 independent resistant Toxoplasma gondii lines after chemical mutagenesis. All 23 of the lines that we examined harbored single point mutations in ␣-tubulin. These point mutations were sufficient to confer resistance when transfected into wild-type parasites. Several mutations were in the M or N loops, which coordinate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(165 citation statements)
references
References 53 publications
3
153
0
2
Order By: Relevance
“…Intact (or completely folded) microtubules containing the luminal densities were present in tomograms of Toxoplasma tachyzoites that were extracted at room temperature with 5% Triton for 30 min, followed by phosphate-buff ered saline adjusted to 2 M NaCl for 60 min before freezing (Fig. 4, C, D, F, and G), indicating that the uncommon microtubule topology is preserved in Apicomplexa and that these microtubules are exceptionally stable (4,5,13). When additionally treated with the microtubule depolymerizing drug oryzalin, microtubules in Toxoplasma extracts appeared shorter, and were occasionally ruptured.…”
Section: Analysis Of Microtubules From Different Species and Isolatedmentioning
confidence: 98%
“…Intact (or completely folded) microtubules containing the luminal densities were present in tomograms of Toxoplasma tachyzoites that were extracted at room temperature with 5% Triton for 30 min, followed by phosphate-buff ered saline adjusted to 2 M NaCl for 60 min before freezing (Fig. 4, C, D, F, and G), indicating that the uncommon microtubule topology is preserved in Apicomplexa and that these microtubules are exceptionally stable (4,5,13). When additionally treated with the microtubule depolymerizing drug oryzalin, microtubules in Toxoplasma extracts appeared shorter, and were occasionally ruptured.…”
Section: Analysis Of Microtubules From Different Species and Isolatedmentioning
confidence: 98%
“…(Dow et al, 2002;Werbovetz et al, 2003)), while GB-II-5 is approximately 5-fold more active against L. donovani axenic amastigotes and about 60-fold more active against T. brucei bloodstream forms than against intraerythrocytic P. falciparum (K. Werbovetz, unpublished data). Experimental evidence indicates that the binding site for oryzalin is on α-tubulin (Anthony and Hussey, 1999;Morrissette et al, 2004). In the apicomplexan parasite Toxoplasma gondii, molecular simulations suggest that the oryzalin binding site consists of α-tubulin residues Arg2, Glu3, Val4, Trp21, Phe24, His28, Ile42, Asp47, Arg64, Cys65, Thr239, Arg243, and Phe244 (Morrissette et al, 2004).…”
Section: Sequences Of L Tarentolae α-And β-Tubulin Genes and Comparimentioning
confidence: 99%
“…This does not necessarily account for the susceptibility differences between kinetoplastid and apicomplexan tubulin to dinitroanilines, as the amino acid at position 42 differs between Plasmodium α-tubulin and all the other tubulins listed in Figure 3 and the amino acid at position 65 differs between the Leishmania and Trypanosoma α-tubulin. Morrissette et al have suggested that amino acid differences at positions other than the binding site causing allosteric effects are responsible for the selectivity of dinitroanilines for plant and protozoal tubulin (Morrissette et al, 2004). Further structure-activity studies and molecular modeling data are required to develop a binding site model for the dinitroaniline sulfanilamides on kinetoplastid tubulin that will facilitate the design of improved ligands for this important drug target.…”
Section: Sequences Of L Tarentolae α-And β-Tubulin Genes and Comparimentioning
confidence: 99%
“…Vale ressaltar que essa espécie possui o biótipo com o único caso conhecido de gene recessivo conferindo resistência aos herbicidas inibidores de mitose (Morrissette et al, 2004). Um biótipo coletado na Malásia possui resistência múl-tipla aos inibidores de ACCase e de EPSPS (Heap, 2005).…”
Section: Introductionunclassified